Anti-Microbial Activity of Hempseed Oil and Sage Oil against Streptococcus mutans and Candida albicans: An In-Vitro Study - Ruchi Agrawal; Yunus Gonal Yusufsaheb; Naveen Narasimhamurthy; Afreen Begum Hasansab Itagi; Reena Kulshrestha; Santosh Rayagouda Patil (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the anti-microbial activity of sage oil and hempseed oil against Streptococcus mutans and Candida albicans. Material and Methods: The sage oil and hempseed oil in pure extract form were collected from an authorized government organization. The anti-microbial activity from the oils was assessed by Kirby-Bauer disc diffusion method. Standard antibiotics Vancomycin and Fluconazole were taken as a positive control for Streptococcus mutans and Candida albicans, respectively. The mean zone of inhibition (ZOI) was measured at 24 hours, 48 hours and 72 hours by HI-MEDIAs antibiotic zone scale. One-way Analysis of variance with Tukey's Post Hoc was applied for statistical analysis. Results: The mean zone of inhibition of sage oil and hempseed oil at 24 hours, 48 hours and 72 hours against Streptococcus mutans was (7.0 ± 4.24, 9.1 ± 3.71 and 8.4 ± 3.02) and (0.0, 3.2 ± 0.75, 1.9 ± 1.24) respectively. The zone of inhibition against Candida albicans 24 hours, 48 hours and 72 hours for sage oil (2.80 ± 1.151, 6.70 ± 1.30 and 6.30 ± 1.44), hempseed oil (0.0, 3.80 ± 0.75, 3.10 ± 0.41). Sage oil presented potential anti-microbial activity against Streptococcus mutans and Candida albicans. Comparing the anti-microbial efficacy, standard antibiotic (Vancomycin/Fluconazole) was more effective than test oils. Conclusion: Test oils showed anti-bacterial and anti-fungal activity against Streptococcus mutans and Candida albicans. Among these, sage oil showed efficacy at 24 hours, while hempseed oil did not show any effect at this time point. Further studies are needed to affirm the same and test their efficacy in different forms and concentrations.